Healthcare Challenges and Future Solutions in Dental Practice: Assessing Oral Antibiotic Resistances by Contemporary Point-Of-Care Approaches - Georgios N. Belibasakis; Bodil K. Lund; Carina Krüger Weiner; Benita Johannsen; Desirée Baumgartner; Daniel Manoil; Margareta Hultin; Konstantinos Mitsakakis (MDPI AG, 2020)
Antibiotic resistance poses a global threat, which is being acknowledged at several levels, including research, clinical implementation, regulation, as well as by the World Health Organization. In the field of oral health, however, the issue of antibiotic resistances, as well as of accurate diagnosis, is underrepresented. Oral diseases in general were ranked third in terms of expenditures among the EU-28 member states in 2015. Yet, the diagnosis and patient management of oral infections, in particular, still depend primarily on empiric means. On the contrary, on the global scale, the field of medical infections has more readily adopted the integration of molecular-based systems in the diagnostic, patient management, and antibiotic stewardship workflows. In this perspective review, we emphasize the clinical significance of supporting in the future antibiotic resistance screening in dental practice with novel integrated and point-of-care operating tools that can greatly support the rapid, accurate, and efficient administration of oral antibiotics.